Differentiation of an interleukin 3-dependent precursor B-cell clone into immunoglobulin-producing cells in vitro. - Kinashi, T (1988)
Precursors to B-cell lines with immunoglobulin genes in the germ-line context have been shown to be capable of generating mature B cells in vivo. We report here that an interleukin 3-dependent precursor B-cell line, LyD9, differentiated in vitro into mature B cells, producing IgM and IgG by coculture with bone marrow accessory (or stroma) cells or with dendritic cells and T cells. Up to 50% of IgM-positive cells, but no Thy-1-positive cells, appeared after the 7- to 10-day coculture. Induced LyD9 cells underwent heterogenous immunoglobulin gene rearrangement and synthesized mRNAs encoding immunoglobulin mu, gamma, and kappa chains. However, these cells did not show any rearrangement of genes encoding the alpha and beta chains of the T-cell receptor. The induction of differentiation by coculture with bone marrow stroma cells was blocked by anti-lymphocyte function-associated antigen 1 or anti-interleukin 4 antibody. These systems are useful for molecular biological studies on regulation of differentiation of bone marrow-derived cells into the B-cell lineage.